Microsatellite DNA markers and uses thereof - Siraj, Siti Shapor; Chan, Soon Choy; Daud, Siti Khatijah; Tan, Soon Guan; Harmin, Sharr Azni (2008)
Simple sequence repeats (SSRs), which are also known as microsatellite DNA repeats, have now been discovered in fish, more preferably the genomic DNA from the Mystus genus, and have been shown to exhibit length polymorphisms. These repeats represent an abundant pool of potential markers for use in genetic characterization of an individual, which includes genetic mapping, population genetics studies and inheritance studies in various breeding programs.